The Imprinted Messenger RNA Expression in Cloned Porcine Pre-implantation Embryos - 박미령; 김봉기; 이휘철; 이풍연; 황성수; 임기순; 우제석(농촌진흥청 축산기술연구소; 조창연; 최순호; 김상우; 고응규 (Journal of animal reproduction & biotechnology (Online), 2010)
The objective of this study was to determine the mRNA expression patterns of several putative imprinted genes in in vivo and in vitro fertilized, parthenogenetic, and cloned porcine preimplantation embryos. Both maternally (Dlk1, IGF2, Peg1/Mest and Ndn) and paternally (IGF2r, H19 and Xist) imprinted genes were selected. We have used reverse transcription polymerase chain reaction (RT-PCR) to investigate gene expression patterns in the porcine embryos. IGF2 transcripts were detected in the most of embryos. In nuclear transfer (NT), Peg1/MEST transcripts showed fluctuating pattern. Dlk1 was only expressed partially from the morula and blastocyst stage of NT embryos. Ndn gene expression was started somewhat early for in vivo embryos. However, the expressions of maternally imprinted genes were similar in all types of blastocysts (NT, in vivo and in vitro fertilized, and parthenogenetic embryos). The IGF2R gene expression level was somewhat irregular and varied among samples. However, for the majority samples of all types of embryos, IGF2R expression was diminished after one- to two-cell stages and reappeared at the morulae or blastocyst stage embryos. H19 gene was only expressed early in parthenogenetic and in vivo embryos. For NT embryos, H19 was only expressed in blastocysts. Xist expression was detected in all blastocysts with the earliest being in vivo 8-cell stage embryos and the last one being NT blastocysts. These putative imprinted genes appeared to have stage specific expression patterns with a fluctuating pattern for some genes (Peg/Mest, IGF2r, H19). These results suggest that stage specific presence of imprinted genes can affect the embryo implantation and fetal development. KCI Citation Count: 2